Polyfullerene Thin Films Applied as NH3 Sensors - Simõis, André Vítor Santos [UNESP]; Roncaselli, Lucas Kaique Martins [UNESP]; Rodrigues de Oliveira, Vinícius Jessé [UNESP]; Medina, Maria Eduarda Rocha Santos [UNESP]; Ramanitra, Hasina H.; Stephen, M.; Silva Agostini, Deuber L. [UNESP]; Hiorns, Roger C.; de Almeida Olivati, Clarissa [UNESP] (FapUNIFESP (SciELO), 2021)
Fullerene is considered to be the third carbon allotrope after diamond and graphite. The study of fullerene derivatives has been growing due to their exceptional electron affinity. This work proposes th study of three different fullerene derivatives, being phenyl-C61-butyric acid methyl ester (PCBM), oligo {(phenyl-C61-butyric acid methyl ester)-alt-[1,4-bis(bromomethyl)-2,5-bis(octyloxy)benzene]} (OPCBMMB) and poly {[bispyrrolidino(phenyl-C61-butyric acid methyl ester)]-alt-[2,5-bis(octyloxy) benzene]} (PPCBMB), and their application as NH3 sensors. Experimental results showed that these materials have a reproducible response to NH3, with PCBM resulting in the highest observed current peak, followed by OPCBMMB and PPCBMB. These results imply that PCBM, OPCBMMB and PPCBMB can be used to produce NH3 sensors.
Keywords: Fullerene; Gas sensors; NH3